De cirurgião plástico a “digital influencer” : como a conquista da beleza é vendida em Sergipe - Teixeira, Eduardo Vieira (2021)
Amid contemporary discussions on the achievement of beauty and its dissemination by Plastic Surgeons on online social media, this research sought to identify the self-promotion actions of Sergipe’s plastic surgeons who use on Instagram, characterizing their use of the platform, investigating ethical issues, and understanding how their activities are managed there. To make it possible, we contextualize the scenario of the relevance of medicine and plastic surgery on social media from the perspective of Foucault (1984, 1988 and 2008), Zorzanelli and Cruz (2018), Schiavo (2014), Eco (2017), Poli Neto and Caponi (2017), Lemos (2019) and Helmond (2015); and then we explain the use of social media by doctors and the nuances of digital content production through the eyes of Latham (2004), Ramalho (2010), Conselho Federal de Medicina (2011), Bourdieu (1986, 2007), Karhawi (2016,2017, 2018), Duffy (2017, 2020), Machado, Burrowes e Rett (2020) and Jenkins, Green and Ford (2014). Our objectives were achieved by conducting a multiple cases study (YIN, 2016a) under holistic and incorporated cases perspectives, through a set of procedures that involved a content analysis (BARDIN, 2016) of the publications shared between July and December of 2019 by 5 plastic surgeons, and semi-structured interviews with 2 other professionals responsible for managing surgeon’s social media. We can see that Instagram is used to generate interactions with followers in different areas, seeking for an approach of ties and symbolic exchanges, as professionals try to balance the exposure of their personal and professional lives, committing excesses of self-promotion able to accelerate the decision-making of potential patients. This work collaborates with the improvement of a poorly explored sector of research in medical advertising, and also shares with the society a reflection on the current standard of beauty, and also assist in the construction of new actions for plastic surgeons, for the Federal Council of Medicine, and for Instagram itself.